Brand Digital Marketing Based on Machine Learning Classification Algorithm - Lin, Ridi (2024 5th International Conference for Emerging Technology (INCET), 2024)
With the rapid development of the Internet and mobile Internet, digital marketing has become one of the important means of major brand promotion. However, the traditional marketing model usually uses static templates and fixed rules for promotion, which is difficult to achieve accurate push and personalized customization. Therefore, this paper proposes a machine learning classification algorithm for innovative marketing strategy evaluation and analysis. Firstly, marketing theory is used to evaluate market demand, and indicators are divided according to the requirements of marketing strategy evaluation to reduce the interference factors in marketing strategy evaluation. Then, the marketing theory evaluates the marketing strategy of enterprise brand promotion, forms a marketing strategy evaluation scheme, and comprehensively analyzes the marketing strategy evaluation results. Empirical analysis shows that brand digital marketing based on machine learning classification algorithm can better improve the effect and conversion rate of digital marketing under certain evaluation criteria and has greater advantages than traditional marketingmodels.